Climate change and gender: what role for agricultural research among smallholder farmers in Africa? - Nelson, V (International Center for Tropical Agriculture, 2010)
This study was commissioned to provide an understanding of the complex impacts climate change will likely have on existing gender and social inequalities. It presents a conceptual framework for understanding the gender dimensions of climate change and smallholder agriculture in Sub-Saharan Africa; it outlines why climate change mitigation and adaptation activities should seek positive, equitable and empowering outcomes for disadvantaged and less powerful groups; and it identifies some of the questions and priorities that can be addressed in agricultural research in order to mitigate these inequities. Commissioned with support from CIAT, the Pan-Africa Bean Research Alliance (PABRA), the Eastern and Central Africa Bean Research Network (ECABREN), the Southern Africa Bean Research Network (SABRN), and the University of Greenwich.